(untitled) (Communications in Computational Physics, 2018)
Variations on space-time Discontinuous Galerkin (STDG) discretization associated to Runge-Kutta schemes are developed. These new schemes while keeping the original scheme order can improve accuracy and stability. Numerical analysis is made on academic test cases and efficiency of these schemes is shown on propagating pressure waves.